A qualitative evaluation of the scientific program in IAPSCON 2014-2018 - Govind V S Murthi; Srinivas Rao Mukkavilli (Wolters Kluwer Medknow Publications, 2020)
Aim: To evaluate the range and scientific nature of oral presentations in the Scientific Program of IAPSCON from 2014-18 Methods: The oral presentations in Scientific Program of IAPSCON from 2014 - 18 were tabulated and categorised as per: type of presentation, Paediatric Surgery related clinical subject heading, nature of the content and scientific quality as per Oxford levels of clinical evidence. Results: Most oral presentations were in the form of Short papers. The most common clinical section and clinical condition presented were Urology and Hypospadias respectively. Clinical management followed by operative management represent the majority of the presentations when categorized by the type of content. Certain sections of clinical practice were not represented at all, notably anterior abdominal wall defects and gastro-oesophageal reflux. Most presentations (82.5%) are in Level 4 and 5 as per Oxford levels of clinical evidence, with Levels 1-3 accounting for 5% of presentations. Minimally Invasive Surgery (including robotic) accounted for 8.4% presentations. Conclusions: This qualitative evaluation shows the variety of oral presentations and areas of greater and lesser interest in the conference meetings. It shows that the scientific quality of the presentations can be improved and highlights certain areas of clinical and scientific research for future consideration.